Cervical interspinous bursitis in active polymyalgia rheumatica. Issue 6 (21st January 2008) - Salvarani, C; Barozzi, L; Cantini, F; Niccoli, L; Boiardi, L; Valentino, M; Pipitone, N; Bajocchi, G; Macchioni, P; Catanoso, M G; Olivieri, I; Hunder, G G
Abstract : Objective: To evaluate the inflammatory involvement of cervical interspinous bursae in patients with polymyalgia rheumatica (PMR) using MRI. Methods: In all, 12 consecutive, untreated new patients with PMR were investigated. Five patients with fibromyalgia, two patients with cervical osteoarthritis and six patients with spondyloarthritis with neck pain served as controls. MRI of the cervical spine was performed in all 12 PMR case patients and in 13 control patients. Two of the four patients with PMR with pelvic girdle pain also had MRI of the lumbar spine. Results: MRI evidence of interspinous cervical bursitis was found in all patients with PMR, and in three patients with fibromyalgia, in two with psoriatic spondylitis and one with cervical osteoarthritis. A moderate to marked (grade ⩾2 on a semiquantitative 0–3 scale) cervical bursitis occurred significantly more frequently in patients with PMR than in control patients (83.3% compared with 30.7%, p = 0.015). In all patients and controls with cervical bursitis the involvement was found at the C5–C7 cervical interspaces. MRI of the lumbar spine showed lumbar interspinous bursitis at the L3–L5 lumbar interspaces in the two patients with PMR and pelvic girdle pain examined. Conclusions: Cervical interspinous bursitis is a likely basis for discomfort in the neck of patients with PMR. The prominent inflammatory involvement of cervical bursae supports the hypothesis that PMR is a disorder of prominent involvement of extra-articular synovial structures.